DNA testing information on YouTube: Inadequate advice can mislead and harm the public. Issue 3 (31st December 2020) - Basch, Corey H.; Hillyer, Grace C.; Wahrman, Miryam Z.; Garcia, Philip; Basch, Charles E.
Abstract: Direct‐to‐consumer (DTC) DNA (i.e., genetic) testing has become very popular, with close to 30 million Americans having used these services. The 100 most widely viewed DNA YouTube testing videos were analyzed to determine whether they are providing adequate information for consumers. The top 100 videos had more than 300 million cumulative views, showing the popularity and reach of the information source. While many videos addressed the specimen collection process, family roots and ancestry, and the prospect of uncovering unexpected information about family or health leading to possible distress, almost none of the videos addressed accuracy or confidentiality issues, which are major issues of DNA testing. It is recommended that further information on those issues be made readily available, and more vigilant oversight by regulatory agencies be implemented. Such oversight should include monitoring what information is and is not readily provided by each company, and the veracity of information being communicated to existing and prospective consumers. We also recommend that for medical issues, clinical genetic testing, along with genetic counseling by genetic counselors, be the method of choice.